PENGARUH MODEL ROLE PLAYING, COLLABORATIVE LEARNING, DAN PROJECT BASED LEARNING BERBASIS INTERAKSI SOSIAL TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS IV - Neng Eka Pebriani; DEK NGURAH LABA LAKSANA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research focuses on analyzing the improvement of fourth-grade students' learning outcomes at SDN 1 Sukawening, Garut Regency, through the initiation of an innovative social interaction-based learning model. This pedagogical intervention specifically applies three different approaches: Role-Playing, Collaborative Learning, and Project-Based Learning (PjBL) in the context of Pancasila Education material regarding rules in the surrounding environment. The implementation of this interactive learning involved the participation of 22 students and was divided into three meeting cycles. The main hope of this research is to provide a real contribution to improving the quality of the learning process at the elementary school level, particularly in efforts to instill Pancasila values from an early age. Evaluation shows that the implementation of the social interaction-based model succeeded in substantially increasing student engagement and resulting in a significant increase in learning outcomes. Furthermore, this model effectively encourages students to be more active, hones collaboration skills, and strengthens individual responsibility. Although issues of passivity were identified in some students, this obstacle was successfully overcome through adjustments to the grouping strategy to ensure equitable participation. Therefore, this study concludes that the social interaction-based learning model is an effective strategy to be applied in the context of fourth-grade interactive learning to foster cooperative attitudes and crucial values for the formation of students' character. Keyword: Innovative Learning; Learning Outcomes, Pancasila Education